2022
DOI: 10.1155/2022/4943413
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] An Adaptive Dance Motion Smart Detection Method Using BP Neural Network Model under Dance Health Teaching Scene

Abstract: As a body movement art, dance has its special form of expression. In terms of dance vocabulary, it can be roughly divided into two parts: external body movement and internal modality. In the process of body movement, it conveys information through silent language and the audience directly feels the information given by the dance image through vision. This is the special way of expressing emotion and meaning in dance art. This paper combines artificial intelligence technology and BP neural network (BPNN) algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Recurrent networks (RNs) provide a very efficient method of time-based sequence management by highlighting relationships between closely related data components in the sequence. Time-varying memory cell and current unit output are equally contributed by the previous BRN units in equation (1).…”
Section: ) Bi-directional Tuned Recurrent Network (Brn)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrent networks (RNs) provide a very efficient method of time-based sequence management by highlighting relationships between closely related data components in the sequence. Time-varying memory cell and current unit output are equally contributed by the previous BRN units in equation (1).…”
Section: ) Bi-directional Tuned Recurrent Network (Brn)mentioning
confidence: 99%
“…This invention promotes a caring and sympathetic learning environment by enabling instructors to modify their teaching tactics appropriately. By using this method, students improve their technical proficiency among their emotional intelligence, which enhances their whole dancing experience and gets students prepared for a variety of creative activities [1]. The modern techniques improve students' understanding of dance as significant medium by using developments in emotion-detection technology and cognitive science.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of scientific and pedagogical literature on the research topic has demonstrated a considerable theoretical base of materials on the use of the latest information technologies in the professional training of specialists in artistic and pedagogical specialties, including specialists in choreography (Chu & Feng, 2021), (Liu, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%